Old Fears, New Hopes. Flemish TV fiction and National Identity in the 21st Century - Alexander Dhoest (Series. International journal of tv serial narratives)
The overarching narrative about TV drama and TV more generally is one of continuous change. Taking a step back, in this paper I reflect on changes and continuities in the past 25 years. Starting in the late 1990s, I discuss the challenges facing European serial drama production as the market increasingly commercialised, digitised, and globalised. From a product typically associated with domestic markets, popular mostly with national audiences, it turned into a transnational commodity, as U.S. drama had been for a long time. Taking the case of Flanders, a small region and TV market, as a starting point, I discuss how these evolutions had an impact on the quantity and quality of drama, with particular attention to the issue of national identity. I argue that, despite many changes and new challenges, including increasing competition, domestic fiction continues to occupy a privileged position in Flanders. Fears about the viability of Flemish drama are not new, but rather the reiteration of old worries, which have challenged the industry – and academics – for at least a quarter century now. Streaming, in particular, carries competition to a new level, but it also creates new possibilities for coproduction and transnational distribution.